1989
DOI: 10.1212/wnl.39.3.434
|View full text |Cite
|
Sign up to set email alerts
|

The EEG response to diffuse and patterned photic stimulation during acute untreated alcohol withdrawal

Abstract: We studied the responses to diffuse and patterned stroboscopic light stimulation prospectively in 49 individuals during acute alcohol withdrawal prior to pharmacologic treatment. Photomyogenic responses (PMR) occurred in only two (4%) of those tested, and photoparoxysmal responses (PPR) never occurred. These findings suggest that PMR occur far less often during alcohol withdrawal than previously thought and that PPR may not be a direct manifestation of alcohol withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Clinically, there may be eyelid flutter, vertical oscillations of the eyelids and eyeballs, and jerks involving the face and head (Noachtar et al, 1999). It most often is seen in tense, anxious individuals and can occasionally occur in alcohol withdrawal (Fisch et al, 1989).…”
Section: Photic Stimulationmentioning
confidence: 99%
“…Clinically, there may be eyelid flutter, vertical oscillations of the eyelids and eyeballs, and jerks involving the face and head (Noachtar et al, 1999). It most often is seen in tense, anxious individuals and can occasionally occur in alcohol withdrawal (Fisch et al, 1989).…”
Section: Photic Stimulationmentioning
confidence: 99%
“…To address the influence of benzodiazepines on identification of photomyoclonic or photoconvulsive responses in patients undergoing withdrawal, Fisch et al (1986) performed EEGs on 49 patients within 48 h of their last drink. All demonstrated some features of withdrawal, but none had received benzodiazepines or other sedatives at the time of EEG recording.…”
Section: Alcohol Withdrawal Seizuresmentioning
confidence: 99%
“…Since generalized seizures may occur during alcohol withdrawal, the expectation could be that the PPR as a generalized discharge may be found in the state. However, Fisch et al 62 never found the PPR in his group of 49 patients in withdrawal.…”
Section: Seizures Associated With Pprmentioning
confidence: 86%